Pembuatan Dan Karakterisasi Ekstrak Kering Simplisia Jati Belanda (Guazuma ulmifolia Lamk.) - Harrizul Rivai; Ayu Hesti Wahyuni; Humaira Fadhilah (STIFARM Padang, 2013)
The research on preparation and characterization of dried leaves extract of simplicia jati belanda (Guazuma ulmifolia Lamk.) has been done. The dry extract is made by adding various ratio of lactose, which is the ratio of the extract and drying with lactose 1x viscous extract, 1½ x viscous extract and extract thick 2x viscous extract. Levels of water soluble compounds the highest value on the dry extract 1:2 was 22.6% ± 0.3434%, while the levels of ethanol soluble compounds the highest value on the dry extract 1:1 was 6.6406% ± 0.2785%, and the highest value content of flavonoids in the dry extract was 1:1 was 1.0047% ± 0.0031%.